How to safeguard the continuous renal replacement therapy circuit: a narrative review - Hu, Chaomin; Shui, Pengfei; Zhang, Bo; Xu, Xin; Wang, Zhengquan; Wang, Bin; Yang, Jie; Xiang, Yang; Zhang, Jun; Ni, Hongying; Hong, Yucai; Zhang, Zhongheng (Frontiers in Medicine, 2024)
The high prevalence of acute kidney injury (AKI) in ICU patients emphasizes the need to understand factors influencing continuous renal replacement therapy (CRRT) circuit lifespan for optimal outcomes. This review examines key pharmacological interventions—citrate (especially in regional citrate anticoagulation), unfractionated heparin (UFH), low molecular weight heparin (LMWH), and nafamostat mesylate (NM)—and their effects on filter longevity. Citrate shows efficacy with lower bleeding risks, while UFH remains cost-effective, particularly in COVID-19 cases. LMWH is effective but associated with higher bleeding risks. NM is promising for high-bleeding risk scenarios. The review advocates for non-tunneled, non-cuffed temporary catheters, especially bedside-inserted ones, and discusses the advantages of surface-modified dual-lumen catheters. Material composition, such as polysulfone membranes, impacts filter lifespan. The choice of treatment modality, such as Continuous Veno-Venous Hemodialysis (CVVHD) or Continuous Veno-Venous Hemofiltration with Dialysis (CVVHDF), along with the management of effluent volume, blood flow rates, and downtime, are critical in prolonging filter longevity in CRRT. Patient-specific conditions, particularly the type of underlying disease, and the implementation of early mobilization strategies during CRRT are identified as influential factors that can extend the lifespan of CRRT filters. In conclusion, this review offers insights into factors influencing CRRT circuit longevity, supporting evidence-based practices and suggesting further multicenter studies to guide ICU clinical decisions.